Peranan Bauran Promosi Pada Cv. Dua Putri Sholehah (Industri Olahan Bawang) Desa Tegalrejo Kabupaten Probolinggo - Ningsih, Revi Rahmawati; Lidyana, Novita (Agrotechbiz : Jurnal Ilmiah Pertanian, 2022)
This study aims to determine the role of the promotion mix on the CV of Dua Putri Sholehah (Onion Processing Industry) in Tegalrejo Village, Probolinggo Regency. The data sources used are primary data and secondary data. Primary data can be the opinion of the subject (person) individually or in groups, the results of observations of an object (physical), events or activities, and test results. While the secondary data uses the company's internal data. CV. Dua Putri Sholehah uses the entire promotional mix, namely Advertising (Advertising) advertising media used by CV. Dua Putri Sholehah is a banner with a target audience of consumers aged 15 years and over, both men and women. Banners are advertising media intended to provide information about CV places and products. Two Daughters of Sholehah. Face-to-Face Sales (Personal Selling) CV. Dua Putri Sholehah carries out promotional activities through personal selling by establishing relationships with customers who have outlets, shops and placing several resselers in several regions. The company distributes its products directly to consumers. Public Relations and Publicity, by conducting social activities and events that involve the community directl. Sales promotion activities are carried out by distributing samples and free trials to consumers who visit CV outlets. Two Princesses of Sholehah or visited the exhibition booth held by the company. CV. Dua Putri Sholehah uses this method to attract new buyers and increase loyalty. The segment to which CV is headed. The two Princess Sholehahs in each of the promotional mixes are the traditional market segment, the modern market segment, the souvenir market segment, the international market segment.Keywords : Mix; marketing; onion preparations